The relevance of marketing in the success of innovations - Abraham Garcia (European Commission, Joint Research Centre (JRC), 2011)
This paper focuses on marketing expenditures and their relation with R&D investments and innovative sales. A higher investment in R&D is associated with the production of a higher quality or faster innovation, with a positive impact on sales and in a macro sense, an increase of GDP. This paper raises the issue that good innovation need a strong marketing effort in order for this innovation to have an impact on sales, it needs to be desired by consumers. This paper finds empirical evidence that marketing expenditures explain a lot of the success of the innovation 0.5 to 0.7% (measured in terms of the elasticity of this effort to innovative sales), even more than the flow of investment in R&D(which counts for 0.3 %). In fact, the size of the coefficient for marketing doubles those found for R&D, a quite surprising result taking into consideration the little importance that marketing has in innovation studies. The paper uses Community Innovation Survey data, the third wave (CIS 3) and set up a system of simultaneous equations like in Crepon et al. (1998).
Keywords: 330